1996
DOI: 10.1021/ja960338m
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Large N 1s Binding Energy in X-ray Photoelectron Spectra of Calcined Carbonaceous Materials

Abstract: Theoretical models and ab initio Hartree-Fock wave functions are used to investigate the N 1s core level binding energies of N-containing calcined carbonaceous materials. Comparison of calculated and experimental values for a series of test molecules reveals that the N 1s core level shift from one compound to another is mainly originated by initial state effects. This permits a systematic study of different situations and allows establishment that three different types of nonoxidized N atoms can be present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
278
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 503 publications
(305 citation statements)
references
References 24 publications
20
278
1
2
Order By: Relevance
“…3) suggests that graphitization of the CS-ACs increased gradually with increasing heat-treatment temperature. The nitrogen atoms incorporated in CS-ACs were examined by X-ray photoelectron spectroscopy (XPS), because it has been suggested that various types of nitrogen atoms, including pyridine-like nitrogen (398.6 eV), pyrrole-like nitrogen (400.5 eV), quaternary nitrogen (401.3 eV), and oxide nitrogen (402-405 eV), are present in nitrogen-containing carbons [18][19][20][21][22]. As the heat-treatment temperature increased, the proportion of pyridine-like N species decreased, and almost disappeared in the case of CS1200-AC, whereas some quaternary nitrogen (401.3 eV) species remained even after heat-treatment at 1200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…3) suggests that graphitization of the CS-ACs increased gradually with increasing heat-treatment temperature. The nitrogen atoms incorporated in CS-ACs were examined by X-ray photoelectron spectroscopy (XPS), because it has been suggested that various types of nitrogen atoms, including pyridine-like nitrogen (398.6 eV), pyrrole-like nitrogen (400.5 eV), quaternary nitrogen (401.3 eV), and oxide nitrogen (402-405 eV), are present in nitrogen-containing carbons [18][19][20][21][22]. As the heat-treatment temperature increased, the proportion of pyridine-like N species decreased, and almost disappeared in the case of CS1200-AC, whereas some quaternary nitrogen (401.3 eV) species remained even after heat-treatment at 1200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…• A pyridinic nitrogen atom substitutes for a carbon atom in an aromatic ring and is bonded to two carbon atoms. None of these two carbon atoms is bonded to atoms other than carbon or hydrogen; see Fig.2c (e.g., Pels et al, 1995;Casanovas et al, 1996) • Ammonium fixed in clay (see Fig. 6d, f).…”
Section: Elemental Isotopic and Thermal Analysesmentioning
confidence: 99%
“…• N-C3 as described for N-Q1 above (Casanovas et al, 1996) • Nitrogen oxide (Pels et al, 1995) • N-C3 as described for N-Q1 above (Casanovas et al, 1996) • A pyrrolic nitrogen atom substitutes for a carbon atom in a non-aromatic ring and is bonded to one hydrogen atom and two carbon atoms. None of these two carbon atoms is bonded to additional atoms other than carbon or hydrogen; see Fig.…”
Section: Elemental Isotopic and Thermal Analysesmentioning
confidence: 99%
See 2 more Smart Citations